Factors in the Transition from Legal to Illicit Drug Use in Young Adults from Northern Mexico - Mayra Selene Ozuna Esprinosa; Josefina Saraí Candia Arredondo; María Magdalena Alonso Castillo; Karla Selene López García; Francisco Rafael Guzmán Facundo (Universidad de Antioquia, 2019)
Objective. This research sought to analyze the predictive effect of personal (personality traits), social (social support and social stigma) and community factors (characteristic of the neighborhood and exposure to consumption) on the transition of drug use in young adults. Methods. Case and control study. The cases were 70 individuals from 18 to 34 years of age who had already transitioned into illicit drug use and the controls were 210 legal drug usuers (tobacco or alcohol) in the same age range  who had not had the transition. A data file was applied along with seven instruments that measured the transition and consumption variables. Results. Marihuana was the illicit drug of highest transition. It was shown that greater personality traits of neuroticism, extraversion, and openness to the experience meant higher probability of drug use transition; while greater personality traits of agreeableness and conscience meant lower probability for the transition. The characteristics of the neighborhood environment and exposure to the opportunity of consumption increase the probability of the drug use transition. Social support and social stigma influenced negatively upon the drug use transition. Conclusion. Personality traits, neighborhood characteristics, exposure to drug use, social support, and the social stigma of drug use are factors that intervene in the transition from legal to illicit drug use   How to cite this article: Ozuna  MS, Candia JS, Alonso MM,  López KS, Guzmán FR. Factors in the Transition from Legal to Illicit Drug Use in Young Adults from Northern Mexico. Invest. Educ. Enferm. 2019; 37(3):e11.